Challenge in Diagnosis and Treatment of Ectopic Hepatocellular Carcinoma: A Case Report and Literature Review - Liu, Qicen; Li, Jingyi; Pan, Yi; Zheng, Xiang; Gao, Bin (Frontiers in Surgery, 2022)
Rarely finding of ectopic hepatocellular carcinoma(EHCC) is be documented. The complicated clinical features and medical prognosis make difficult of diagnosis and treatment. The describing of the patient was a 59-year-old male presented with epigastric discomfort and regurgitation of gastric acid. Enhanced CT-scan revealed a 1.8×1.4cm mass in the distal pancreas without any positive finding in liver. And postoperative MRI-scan was performed but not revealing any evidence of tumor in the liver. The mass was resected in toto, meanwhile a 1.0×1.0cm mass in body of stomach was found which was removed simultaneously. Histopathology showed the tumor in the distal pancreas were ectopic hepatocellular carcinoma(EHCC) and the nodule in the stomach was gastrointestinal stromal tumors(GISTs). The patient had an uneventful postoperative recovery and alive without recurrence over 7 years since surgery. Owing to our knowledge, we believe that this is the first report of combining ectopic hepatocellular carcinoma with GISTs and the second longest disease-free survival time of EHCC for literature we researched. Here we present a case of a rare EHCC in pancreas and review the current literature about EHCC. Operation was an effective treatment for EHCC of curable patients. EHCC with metastasis still need more practice for the poor prognosis.